THE LANDSCAPE OF OURO PRETO (MG, BRAZIL) THROUGH ANALYSIS OF ANTHROPIC ACTIVITIES IN RELATION TO THE ENVIRONMENTAL CONSERVATION - Silva, Rossi Allan; Pereira, José Aldo Alves; Bueno, Inácio Thomaz; Borges, Luís Antônio Coimbra; Acerbi Júnior, Fausto Weimar (Floresta, 2018)
Understanding the complex interaction among landscape elements can improve the management of environmental conservation and anthropic activities. The aim of the present study was to develop a methodology that assists in the planning and management, harmonizing the conservation of natural areas with anthropic activities in the city of Ouro Preto (state of Minas Gerais, Brazil). The methodology used the weighted overlay algorithm of the ArcMap™ software, which weights among land use characteristics. In the present study, the following classes were used: slope; relief; soil; landscape ownership by individuals; presence of protected areas; economy; and type of management applied to the preservation or conservation of forests and fields. The most relevant anthropic activities (contained in the classes) were simulated, to the detriment of the forest reduction, according to their spatial locations. Consequently, a map with five weights was obtained, which were verified in the field with their respective descriptions. The physical changes occurred as a reflection of the economy, promoting environmental effects, especially related to the mining, tourism, agricultural and livestock activities, besides conservation of natural areas. All of them require ideally a shared management. The interactions among simulated classes aid to increase information in future planning. Understanding the anthropic and natural processes, which have taken place by either consolidation or isolation along the territory, can assist decision-making on the current directions and in the definition of future proposals. It was noticed that the landscape needs a management which creates sustainable alternatives for anthropic activities.